Nurses' Experiences of Burnout in the Emergency Room of a Hospital in Medan, Indonesia: A Descriptive Phenomenological Study - Setiawan Setiawan; Sarifa Aini (Caring: Indonesian Journal of Nursing Science, 2026)
Burnout is a chronic state of physical and emotional exhaustion experienced by nurses as a result of prolonged exposure to work-related stress, particularly in high-demand environments such as emergency departments. Although quantitative data on its prevalence are available, the lived experiences and personal meanings that emergency nurses associate with burnout within Indonesia’s cultural and institutional context remain poorly understood. The purpose of this study was to phenomenologically explore the experiences of burnout among nurses in the emergency room of a hospital in Medan, Indonesia. The study used a descriptive phenomenological approach. Ten nurses were selected using a purposive sampling technique. Data were collected through face-to-face, in-depth interviews using an interview guide. Methodological trustworthiness was ensured through the application of explicit reflexive bracketing, prolonged engagement, and member-checking procedures. The interview transcripts were systematically analyzed using Colaizzi’s seven-step descriptive phenomenological method. The findings revealed five themes related to nurses experience on burnout in an emergency room: 1) receiving pressure and negative attitudes from patients and families, 2) undergoing high workloads and minimal appreciation, 3) experiencing negative feelings and low motivation, 4) facing internal obstacles and barriers, and 5) managing sources of stress and improving self-quality. The findings of this study indicate that burnout is a complex experience that affects nurses’ physical and emotional well-being, while also influencing their work motivation and sense of professional meaning. Hospital management should establish structured psychological support systems, ensure objective workload redistribution, and implement clear workplace violence prevention policies to protect nurses’ well-being and maintain the quality of patient care. Keyword: Burnout, Descriptive Phenomenology, Emergency Room, Nurse, Hospital